2015
DOI: 10.1108/caer-02-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in financing of agri-food value chains in China and India

Abstract: Purpose – The purpose of this paper is to synthesize lessons from the agricultural value chain models and their associated financing mechanisms in China and India as to provide policy recommendations on how best to facilitate development of efficient and inclusive value chains. Design/methodology/approach – The paper builds on a review of the existing literature on agricultural value chains and their financing mechanisms, and draws lesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 24 publications
2
45
0
1
Order By: Relevance
“…Many export-oriented agribusiness firms have promoted producers' associations to control over the production process to enable the farmers to comply with safety standards of the importing countries. For example, the Agrocel Industries secure their requirement of organic cotton and Basmati rice through producers' associations (Chen et al 2015); and Mahagrapes (an apex organization of grape growers) sources grapes through cooperatives (Roy and Thorat 2008).…”
Section: Value Chain Framework For Agricultural Commoditiesmentioning
confidence: 99%
“…Many export-oriented agribusiness firms have promoted producers' associations to control over the production process to enable the farmers to comply with safety standards of the importing countries. For example, the Agrocel Industries secure their requirement of organic cotton and Basmati rice through producers' associations (Chen et al 2015); and Mahagrapes (an apex organization of grape growers) sources grapes through cooperatives (Roy and Thorat 2008).…”
Section: Value Chain Framework For Agricultural Commoditiesmentioning
confidence: 99%
“…A business model is defined as a way in which the activities of value chain actors are being organized [29]. A business model, therefore, organizes the value chain actors in order to reduce transaction costs, information sharing facilities to avoid asymmetric information, and innovative financial products to manage risks along the chain [30]. In the past, several studies have developed financing models to strengthen and extend financial products and services to the agricultural sector [24,[30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…A business model, therefore, organizes the value chain actors in order to reduce transaction costs, information sharing facilities to avoid asymmetric information, and innovative financial products to manage risks along the chain [30]. In the past, several studies have developed financing models to strengthen and extend financial products and services to the agricultural sector [24,[30][31][32][33][34][35]. Previous studies on agricultural value chain finance, have identified that chain integration, strategic partnering, supporting services and product range related factors influence the value chain competitiveness [31].…”
Section: Introductionmentioning
confidence: 99%
“…Logistics financial development. Rural finance has a positive transmission effect and driving effect on agricultural products logistics (Clapp, 2014), which is the reasonable measure to break through the development bottleneck and to resolve the financing difficulty in the process of agricultural products circulation (Chen et al, 2016).…”
Section: Identification Of Key Influencing Factors Of Development Of mentioning
confidence: 99%